Estudo dos mecanismos e mediadores envolvidos no efeito antinociceptivo e anti-inflamatório das proteínas isoladas do látex de Himatanthus drasticus em camundongos - Marques, Larisse Mota (2017)
There is a constant search for analgesic drugs to control the pain while promoting as few side effects as possible. This study aimed to evaluate the effect of a latex protein fraction from Himathantus drasticus (HdLP) in experimental models of nociception after approval by the CEUA/UFC (n° 51/14). Male Swiss mice (20-25g) were pretreated with HdLP e.v. 30 min before noxious stimuli and it were evaluated by measures of nociceptive behavior. HdLP (0.5, 5 and 10 mg/kg) was investigated in the test models of nociception induced by acetic acid (i.p), formalin (i.pl), capsaicin (i.pl.) or glutamate (i.pl). Involvement of opioid system was evaluated using formalin test by prior injection of naloxone s.c. (2 mg/kg). To assess thermal nociception, mice were placed on a hot plate (55 oC) 30, 60, 90 and 120 minutes after HdLP treatment (0.5, 5 and 50 mg/kg). The HdLP antihyperalgesic effect (0.5, 5 and 50 mg/kg) was evaluated using mechanical models of hyperalgesia induced by carrageenan, PGE2 or dopamine by the electronic Von Frey method 1, 3 and 5 h after carrageenan or 3 h after PGE2 or dopamine. Anti-inflammatory effects were investigated using the test of paw edema induced by carrageenan. Animals were euthanized 3 h after carrageenan and paws were collected for evaluation of myeloperoxidase activity (MPO), inflammatory mediators production (TNF-α, IL-1β, KC and IL-10), histopathological analysis, Western blot analysis of TNF-α, immunohistochemical assays (COX-2, NOSi) and levels of oxidative stress (MDA, GSH, SOD, CAT). Involvement of the NO/cGMP/K+ channels pathway was investigated by prior administration of L-NMMA, ODQ or glibenclamide, respectively, in PGE2-induced hyperalgesia. To investigate mechanisms underlying HdLP anti-inflammatory action, we investigated the effect of HdLP (25, 50, 100 μg/ml) on LPS-induced responses in a murine macrophage cell line, RAW 264.7. Statistical analyzes were performed using ANOVA/Newman Keuls or Kruskal Wallis/Dunns test and p<0.05 was considered significant. HdLP significantly reduced the nociception induced by acetic acid, formalin (in both phases), capsaicin and glutamate in a dose-dependent manner. This effect was reversed by previous administration of naloxone in the formalin test. HdLP was found to be effective in hot plate test, carrageenan-induced hyperalgesia and paw edema in a time- and dose-dependent manner. HdLP also reduced PGE2-and dopamine-induced hyperalgesia. The effect of HdLP on PGE2-induced hyperalgesia was reversed by prior administration of L-NMMA, ODQ and glibenclamide. Pre-treatment with HdLP decreased MPO activity and TNF-α and IL-1β production and increased IL-10 release. TNF-α expression by western blot and COX-2 expression by immunohistochemistry were decreased and SOD activity was increased. There was no change in KC, CAT, GSH and MDA levels or NOSi expression and NO release in vitro. The present results suggest that HdLP exhibits antinocieptive effect in mice by inhibiting neutrophil migration, release of proinflammatory cytokines (TNF-α, IL-1β) and expression of inflammatory mediators (COX-2), as well as releasing anti-inflammatory cytokine IL-10. Furthermore, opioid system and L-arginine/NO/cGMP/K+ pathway seems to be responsible, at least in part, for the antinociceptive effect of HdLP.